2016
DOI: 10.15171/jnp.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hematuria on the outcome of immunoglobulin A nephropathy with proteinuria

Abstract: Background: The relationship between hematuria and histological lesions, the effect of hematuria on response to steroid therapy, and the outcome in patients with immunoglobulin A nephropathy (IgAN) remain undetermined. Objectives: The aim of this study was to clarify the effect of hematuria on histological findings, response to steroid treatment, and the outcome in IgA nephropathy. Patients and Methods: Seventy-five patients with IgAN and proteinuria > 1 g/day and treated with prednisolone were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…Although some studies suggested a significant influence of hematuria on the risk of developing ESRD, 6,9,19,20 others could not confirm this finding. [21][22][23][24] However, the robustness of these studies was reduced by the way in which hematuria was evaluated (at the onset of the disease, at the time of renal biopsy, or by cross-sectional studies) without longitudinal data. 23,24 In other studies, urine dipsticks were used, and the magnitude of hematuria was not quantified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies suggested a significant influence of hematuria on the risk of developing ESRD, 6,9,19,20 others could not confirm this finding. [21][22][23][24] However, the robustness of these studies was reduced by the way in which hematuria was evaluated (at the onset of the disease, at the time of renal biopsy, or by cross-sectional studies) without longitudinal data. 23,24 In other studies, urine dipsticks were used, and the magnitude of hematuria was not quantified.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] However, the robustness of these studies was reduced by the way in which hematuria was evaluated (at the onset of the disease, at the time of renal biopsy, or by cross-sectional studies) without longitudinal data. 23,24 In other studies, urine dipsticks were used, and the magnitude of hematuria was not quantified. 20 At the end of follow-up, 17.2% of our patients had reached ESRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Cox proportional hazard model, the corresponding HR was 0.85 (95% CI, 0.64–1.14; p = .28). Of 2 studies from the same center in Japan [ 14 , 33 ], the magnitude of hematuria at biopsy (per 20 RBCs/HPF increase) was evaluated in IgAN patients with proteinuria (> 1 g/day) and mild proteinuria (< 0.5 g/day). The HRs were 0.75 (95% CI, 0.55–1.00; p = .053) and 1.16 (95% CI, 0.89–1.46; p = .247), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, proteinuria at onset was not associated with bad prognosis, probably because it represents the consequence of the acute inflammation, reversible with steroid therapy. Gross hematuria, per se, is not prognostic (119), but persistence of severe microscopic hematuria has recently been considered a risk factor (120). Glomerular filtration rate at biopsy is a predictor of the need for dialysis in adults (118,(121)(122)(123)(124).…”
Section: Natural History and Prognosismentioning
confidence: 99%